El marketing mix y su relación con las ventas en la empresa “Capinuri Amazonia Tours” - Iquitos 2024 - Jarama Vasquez, Deborah Sofia (2025)
The results determined the opinion regarding the Marketing mix as follows: they agree with the product (58.3%), with the price they totally agree (58.3%), with the place they totally agree (50). .0%), with the promotion (58.3%) agree. In addition, 41.65% reached a level of complete agreement in its components, the gap of 58.35% remains to be met. The opinion regarding Sales was the following: they agree with the sales management (58.3%), with the type of sales they totally agree (41.7%), with the sales technique they totally agree the (41.70%). In addition, sales reached the level of complete agreement in its components at 36.13%, the gap of 63.87% remains to be covered. It was concluded that the marketing mix is related to sales with (p=0.015)